1985
DOI: 10.1128/mcb.5.8.2070
|View full text |Cite
|
Sign up to set email alerts
|

Common regulatory elements control gene expression from polyoma early and late promoters in cells transformed by chimeric plasmids.

Abstract: In a previous report we showed that transcripts initiating from the late promoter of integrated polyoma plasmids could be detected at significant levels when neomycin resistance (neo) coding sequences were linked to this promoter. In this report we used chimeric plasmids that contain either a limited portion of the polyoma genome or deletions within the polyoma noncoding regulatory region to determine the sequence requirements for late promoter activity in this system. We observed no absolute requirement for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
32
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 58 publications
2
32
0
Order By: Relevance
“…The replication in permissive cells of many of the mutants used in these studies has been previously described (13,31,32,52). In this study, several of the mutants were either tested for the first time or reexamined for their ability to replicate in WOP mouse cells (13).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The replication in permissive cells of many of the mutants used in these studies has been previously described (13,31,32,52). In this study, several of the mutants were either tested for the first time or reexamined for their ability to replicate in WOP mouse cells (13).…”
mentioning
confidence: 99%
“…Also, the relative affinities of Py and SV40 T Ags for binding sites within their respective ori regions are apparently dissimilar (12,14,28,47). Moreover, while both viruses encode enhancer elements, the Py enhancer is almost directly adjacent to the late boundary of the ori region and consists of a series of discrete elements that bear homologies to other enhancer elements including those of SV40, adenovirus Ela, and mouse immunoglobulin genes (2,22,23,26,31,38,46,51,53). By contrast, the SV40 enhancer, a 72-bp repeated sequence (see reference 22 and references therein), is separated from the core ori by a series of G+C-rich sequences (the 21-bp repeats) that form a distinct transcriptional control element to which the cellular transcription factor, Spl, binds (17) and that is lacking in the Py genome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Here, by using affinity columns containing either DNA polymerase ac/primase or Py T antigen, we present evidence that supports this suggestion. Furthermore (24), and pSVS contains the entire SV40 genome inserted at the BamHI site of pBR322. The incubations were carried out at 33 and 37°C for Py and SV40 replication, respectively.…”
mentioning
confidence: 99%
“…(ii) An enhancer region, originally defined as the 244 bp between the BcII (bp 5021) and PvuII (bp 5264) restriction enzyme sites (17,81), has been subdivided into two unrelated but functionally redundant elements, enhancer A and enhancer B, both of which are capable of stimulating transcription of heterologous genes in an orientation-and position-independent manner (42). Studies with gel retention and nuclease mapping assays have identified several cellular protein factors that bind specifically to the B enhancer (7,26,70 (9,38) and in vivo (2,32,40) and that at least some of the elements of the polyomavirus early promoter, including portions of the enhancer, may regulate the levels of transcription from the late promoter of that virus (8,13,(52)(53)(54).…”
mentioning
confidence: 99%